Pea-Protein-Stabilized Emulsion as a High-Performance Cryoprotectant in Frozen Dough: Effects on the Storage Stability and Baking Performance - Diming Li; Youqing Shi; Zhihan Ouyang; Yongxin Teng; Boru Chen; Yingying Chen; Yufan Luo; Nan Zhang; Nandan Kumar; Yonghui Li; Bin Li; Xiangwei Zhu (Foods)
The use of oil-in-water (O/W) emulsion has drawn increasing attention in the baking industry. Compared with some of the well-recognized functionalities, such as textural improvers and flavor carriers, its cryoprotective behavior in frozen dough has not been extensively investigated. Herein, this study reported a pea-protein (PP)-stabilized O/W emulsion with good freeze–thaw stability and evaluated its effectiveness as a high-performance dough cryoprotectant. Specifically, the emulsions were stabilized by 2, 3, and 4 wt% of PP (PP-2, -3, and -4, respectively) and incorporated into frozen doughs, whose cryoprotective effects were systematically evaluated in terms of dough storage stability and baking performance after 4 weeks of storage. Results showed that the frozen dough with PP-3 emulsion exhibited the most uniform water distribution and reduced content of freezable water as reflected by the results from differential scanning calorimetry and low-field nuclear magnetic resonance analyses. Moreover, the PP emulsion helped to maintain the integrity of the gluten network, thus enhancing the dough elasticity. Accordingly, the emulsion-added bread samples exhibited significantly improved loaf volume and textural properties (e.g., softness) and less baking loss. Our findings highlighted the potential of PP emulsion as a viable and high-performance dough cryoprotectant.